Chemical Composition and Biological Properties of New Romanian Lavandula Species - Ionuț Georgică Marchidan; Alina Ortan; Simona Marcu Spinu; Sorin Marius Avramescu; Ionela Avram; Radu Claudiu Fierascu; Narcisa Babeanu (MDPI AG, 2023)
The aims of the present study were to evaluate for the first time the chemical composition and antioxidant, antibacterial, antifungal and antiproliferative potentials of the Romanian George 90 lavender species, as well as parental species, L. angustifolia and L. latifolia. The L. angustifolia, L. latifolia and George 90 essential oils were analyzed by GC-MS/MS and the L. angustifolia, L. latifolia and George 90 hydroalcoholic extracts were analyzed by HPLC-DAD. The antioxidant, antibacterial, antifungal and antiproliferative assays revealed that all the investigated species showed significant activities. The results highlighted the chemical composition and the promising biological potentials of the L. angustifolia, L. latifolia and George 90 lavender species, validating their ethnomedicinal value, which offers potential applications as natural drugs.